A Study on Talent Management and its Impact on Organization Performance- An Empirical Review - Prof. Pushpa Hongal; Dr. Uttamkumar Kinange (International Journal of Engineering and Management Research, 2020)
These days organization’s talent is its primary source of competitive advantage. Performance of organization depends upon performance of its employees. If employees of an organization possess unique competence, that will differentiate them from their competitors. In this competitive environment retention of talented workforce is a major task for HR managers along with acquisition. Talent management is a very complex and critical task. Right Talent acquisition makes organization strategy more strong. The current global economic situation has increased overall jobseekers in employment market worldwide, but there is still notable talent shortage in different sectors and different countries, this leads to increase the problem of “Talent Mismatch”.As today’s corporate world requires a person with multitasking skill, talent acquisition is becoming very difficult. As a result, finding the “right” person for a particular job is becoming more challenging. Not only acquisition even retention of talented workforce has become greatest challenge for organization. Today’s changing landscape of business requires its HR to act more strategically to build employee engagement which is a great tool for talent management. Talent Management focuses on how individuals enter; move up across or out of the organization. Talent Management will succeed with the support of strong organization structure. As better talent can change the future of business, Talent Management has to be given predominant role in organization. If organization implements talent management strategies effectively, that enhances employee’s engagement which in turn helps to improve organization performance. Higher the employee engagement higher the productivity. This present study aims to identify the relationship between talent management and organization performance. This study is based on empirical research evidence build by literature reviews carried out in this direction. Researcher is intended to use different articles, research papers and literatures in order to identify the positive relationship between talent management and organization performance. This empirical research paper will provide insights to HR managers to build Talent management as a Strategic tool to build employee engagement and thereby improving organization performance.